Building a better 'comic theory': Shortcomings of theoretical research on comics and how to overcome them. Issue 1 (1st April 2014) - Cohn, Neil
Research on the understanding of 'how comics work' has grown tremendously over the past twenty years, with more articles and books emerging each year. Much of this research has discussed comparisons between comics and language, and/or has speculated on comics' cognition. However, much of this research faces limitations, which hamper the seriousness of the endeavour and reflect the youth of this emerging field. This article points out these deficiencies that pervade theories about comics. These include inadequate background research, overly general and unsupportable claims, a lack of adequate evidence, and limitations for research methodologies. To address these concerns, I draw from over 50 years of research from linguistics and cognitive science to inform how the field of 'comic theory' can move forward. In particular, I outline two primary ways of progressing with this line of research: (1) explicit manipulation of the component parts of the structure used in comics and (2) cataloguing actual comics for various theoretically relevant phenomena. This data-driven approach is offered as a guiding vision for future works on the understanding of 'how comics work'.